Study of total antioxidant capacity of red raspberry (Rubus idaeous L.) shoots - Maslov, Olexander Yu.; Komisarenko , Mykola A.; Golik, Mykola Yu.; Kolisnyk, Sergii V.; Altukhov , Alexander A.; Baiurka, Sergii V.; Karpushina, Svetlana A.; Tkachenko, Oksana; Iuliia, Kolisnyk (Vitae, 2023)
BACKGROUND: Today, cardiovascular, oncological, and neurodegenerative diseases are the main causes of death in the world, according to official World Health Organization (WHO) statistics. Antioxidants are used to treat and prevent these diseases. In order to develop optimal technology for obtaining drugs based on plant extracts with antioxidant action, it is necessary to determine the total antioxidant capacity of raspberry shoots. OBJECTIVES: The study aimed to determine the total antioxidant capacity of red raspberry shoots, study the content of biologically active substances (BAS), and the antioxidant activity of red raspberry shoot extracts obtained during subsequent exhaustive extraction. METHODS: The number of phenolic compounds, catechins, flavonoids, and hydroxycinnamic acids was determined by a spectrophotometric analysis method, whereas organic acids were determined by the alkalimetric method in red raspberry shoot extracts; the antioxidant activity of obtained extracts was evaluated by potentiometric method. RESULTS: The total antioxidant capacity of red raspberry shoots was 164.12 mmol-equiv./m dry weight, the sum of the total content of phenolic compounds was 24.40 mg gallic acid (GA)/mL, catechins – 21.36 mg epigallocatechin-3-O-gallate (EGCG)/mL, flavonoids – 0.77 mg rutin (R)/mL, hydroxycinnamic acids derivatives – 2.56 mg chlorogenic acid (ChA)/mL and organic acids – 1.88 mg citric acid (CA)/mL in red raspberry shoot extracts obtained during subsequent exhaustive extraction. The analysis showed that there is a very high positive correlation between antioxidant activity and total phenolic compounds, catechin, flavonoid, hydroxycinnamic acids derivatives, and organic acids content in red raspberry shoot extracts. CONCLUSIONS: Total red raspberry shoots' antioxidant capacity has been determined. The study results can be used to develop optimal technology for obtaining drugs based on the extract of red raspberry shoots, which has an antioxidant effect.